Gene signatures predictive of response to radiotherapy in prostate cancer: a new step towards precision medicine - Lombardi, Angela; Grimaldi, Anna; Caraglia, Michele (Translational Cancer Research, 2017)
In the era of personalized medicine, there is significant emphasis on the development of companion diagnostics and/or molecular signatures to guide therapeutic decisions (1). For example, two recurrence risk signatures (Oncotype Dx® and Mammaprint) are commonly used to guide chemotherapy in women with node-negative breast cancer (2-5). An evolution of Oncotype® (that is a centralized method of determination of the gene signature in breast cancer) is EndoPredict. The latter is a not centralized method of genotyping of the breast cancer that associates a signature of genes to the clinical staging of the patients and that was recently demonstrated to give higher performance if compared with the other well established genotyping system Oncotype. In fact, the test can predict whether breast cancer will spread in women with estrogen receptor positive, HER2 negative (ER+/HER2–) disease (6).